A paisagem na ruralidade brasileira: considerações teórico-metodológicas para uma pesquisa multidisciplinar aplicada - Claudia Ribeiro (Confins, 2015)
Landscape is one of the useful thought categories to improve reflections about complex and multifold actual Brazilian rurality. The paper shows and discusses main concepts and methods assumed by multidisciplinary research that deals with both themes. The main question is whether the landscape – as a dynamic process linked to agricultural activities – could be recognized by this rural population, also as common good in the place. Vila Seca and Criúva, rural districts of the town of Caxias do Sul, at Rio Grande do Sul, Brazilian southernmost state, were empirically picked as the study area. Socio-environmental conflicts events between family farming activities and urban practices motivate this research. Its results are briefly presented, coming from an ethnographic approach with participant observation. Fieldwork was done at celebrations cycle of the Holy Spirit, with attention categories defined by study of agrarian systems, in addition to empirical criteria used for detection of the landscape notion.